Living in the Limelight. - Kushner, D.
Napster may be dead, but Mark Gorton and his company are making sure the file-sharing revolution it sparked lives on through LimeWire. LimeWire is transforming the ripple of grass-roots computer networking that began with Napster a few years ago into a cultural and, inevitably, an economic tidal wave. This article briefly discusses the career of Mark Gorton and his involvement with setting up Napster, Gnutella, and LimeWire, and the prospects of the file sharing technology.
Keywords: Gnutella; LimeWire; Mark Gorton; Napster; Computer networking; File-sharing.